Green Accounting as a Risk Mitigation Measure Ecology in The Biopharma Industry (Study at PT Daewoong Infion) - Herlinda Nia Audina; Sri Trisnaningsih (Economics and Business Journal (ECBIS), 2026)
This study aims to analyze the application of green accounting in hazardous waste management and its role in mitigating ecological risks in the biopharma industry, with a case study at PT Daewoong Infion. The background of the study is driven by the increasing risk of environmental and health pollution due to hazardous waste generated by the biopharmaceutical production process, as well as the limitations of conventional accounting systems in capturing ecological costs and impacts. This study uses a qualitative approach with a case study design, through primary data collection in the form of in-depth interviews with key informants and field observations, as well as secondary data from company documents and related regulations. Data analysis was conducted descriptively and interpretively to identify green accounting practices, environmental cost components, and ecological risk mitigation mechanisms. The results show that PT Daewoong Infion has implemented green accounting through the recognition and recording of hazardous waste management costs, pollution control, and environmental disclosure, which contributes to increased regulatory compliance, waste management efficiency, and ecological risk reduction. In addition, these practices strengthen the company's legitimacy and meet stakeholder expectations, in line with legitimacy theory and stakeholder theory. This study concludes that green accounting serves as an effective managerial and reporting instrument in integrating economic objectives and ecological responsibility, thereby supporting the operational sustainability of the biopharma industry. These findings recommend strengthening environmental cost measurement systems and reporting transparency to enhance sustainable ecological risk mitigation.